(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Living in the 21st century a lot of people think that they are living in a fully developed world. However, very few people know that there are still so many places in the world where people suffer because of the injustice in their lives. The problems with inequality and discrimination exist up to our days, and in some places, it is more severe than in others. In my opinion, the topic of social inequality is essential in order to make the world a better place for everyone.